Territorial and sectoral development of socio-productive infrastructure of the West Kazakhstan region (Journal of Geography and Environmental Management, 2021)
The socio-productive infrastructure system is the basis of the territorial organization of the economy and population of the country and its regions. The territorial framework of different-level socio-economic systems is formed based on a socio-productive infrastructure. Respectively, the territorial and sectoral development of socio-productive infrastructure of the regions of Kazakhstan determines the level of competitiveness of their territorial socio-economic systems and reflects regional and intra-regional characteristics of the territorial organization of a society.  The aim of the work is to analyze the impact of the main factors, identify the territorial and sectoral location and determine the main priority areas of territorial and sectoral development of the socio-productive infrastructure of the West Kazakhstan region.The article proposes the author's approaches to assessing the territorial and sectoral development of socio-productive infrastructure in the region. The main results of the analysis of the current state of territorial and sectoral development of socio-productive infrastructure of West Kazakhstan region are presented. The main factors of development and their impact on the territorial location of socio-productive facilities have been considered. The features of territorial localization of fixed assets were revealed and the typology of administrative districts of the West Kazakhstan region according to the level of the development of socio-productive infrastructure was carried out. The main priority directions of territorial and sectoral development of socio-productive infrastructure of the West Kazakhstan region were determined and proposed.The conducted research shows that the West Kazakhstan region is characterized by a high indicator of territorial localization of social and industrial infrastructure. In 2019, 96.7% of fixed assets were localized in the territory of Burlinsky district and Uralsk city administration, and 1.1% and 0.7% of infrastructure facilities of the region are located in Baiterek district and Terektinsky district. The remaining 9 administrative districts, which occupy 85.7% of the territory of the West Kazakhstan region, account for only 1.5% of fixed assets. There are also significant differences in the sectoral structure of socio-productive infrastructure of administrative districts. The typology revealed that out of 13 administrative districts the maximum level of development of socio-productive infrastructure is characteristic of 2, high – 2, medium – 3 and low – 6 districts of the region. In this regard, the priorities of territorial and sectoral development of socio-productive infrastructure of West Kazakhstan region should be aimed at developing a network of infrastructure facilities of 9 administrative districts located in the east, south, south-west, west and north (Tashkaly district).The results of the research can be used by state line ministries of the Republic of Kazakhstan and local executive bodies of the West Kazakhstan region in the development of perspective directions of territorial and sectoral development of social and industrial infrastructure of the region.
Keywords: socio-productive infrastructure,; territorial and sectoral development,; West Kazakhstan region,; territorial localization,; fixed assets.